Antroposchermi. Forme del continuum fisico-virtuale nella poesia italiana (ENTHYMEMA, 2020)
This paper aims to identify the rhetorical strategies and the metaphors used within the representation of virtual reality beyond the field of digital poetry, through a screening of contemporary Italian poetry. Starting with a preliminary investigation on the metaphorical conversion of electronic devices into disturbing pets, the paper collects examples of water-surfaces as similes frequently adopted for the screen. The interaction with the Web 2.0 has been interpreted as a virtual capsule experience, where the subjects find themselves isolated and framed in a disintegrated relation with their surroundings. Hence I try to verify the consequences of such experience, speculating that poetical writing has been translating those characteristics into a redefinition of the stanza (as a textual capsule), the abundance of the figures of speech and the displaying of reversible textual sequences.
Keywords: contemporary Italian poetry; digital culture; capsule; Pokémon; poetry and technology